A Retrospective, Multicenter, Long-Term Follow-Up Analysis of the Prognostic Characteristics of Recurring Non-Metastatic Renal Cell Carcinoma After Partial or Radical Nephrectomy - Kim, Sung Han; Park, Boram; Hwang, Eu Chang; Hong, Sung-Hoo; Jeong, Chang Wook; Kwak, Cheol; Byun, Seok Soo; Chung, Jinsoo (Frontiers in Oncology, 2021)
This study aimed to compare the cancer-specific survival (CSS) and overall survival (OS) of nephrectomized patients with non-metastatic renal cell carcinoma (nmRCC) and local recurrence without distant metastasis (LR group), those with metastasis without local recurrence (MET group), and those with both local recurrence and metastasis (BOTH group). This retrospective multicenter study included 464 curatively nephrectomized patients with nmRCC and disease recurrence between 2000 and 2012; the follow-up period was until 2017. After adjusting for significant clinicopathological factors using Cox proportional hazard models, CSS and OS were compared between the MET (n=50, 10.7%), BOTH (n=95, 20.5%), and LR (n=319, 68.8%) groups. The CSS and OS rates were 34.7% and 6.5% after a median follow-up of 43.9 months, respectively. After adjusting for significant prognostic factors of OS and CSS, the MET group had hazard ratios (HRs) of 0.51 and 0.57 for OS and CSS (p=0.039 and 0.103), respectively, whereas the BOTH group had HRs of 0.51 and 0.60 for OS and CSS (p <0.05), respectively; LR was taken as a reference. The 2-year OS and CSS rates from the date of nephrectomy and disease recurrence were 86.9% and 88.9% and 63.5% and 67.8%, respectively, for the LR group; 89.5% and 89.5% and 48.06% and 52.43%, respectively, for the MET group; and 96.8% and 96.8% and 86.6% and 82.6%, respectively, for the BOTH group. Only the LR and BOTH groups had significant differences in the 2-year OS and CSS rates (p < 0.05). In conclusion, our study showed that the LR group had worse survival prognoses than any other group in nephrectomized patients with nmRCC.